IMPROVING KNOWLEDGE AND SKILLS ON MEDICAL NUTRITION THERAPY IN TYPE 2 DIABETES MELLITUS PATIENTS IN AGRICULTURAL COMMUNITIES - Angraini, Dian Isti; Carolia, Novita; Mayasari, Diana; Imantika, Efriyan (Universitas Nahdlatul Ulama Surabaya, 2025)
The prevalence of type 2 Diabetes Mellitus continues to increase, including in agricultural communities (farmers). Low treatment compliance can result in increased complications, morbidity and mortality. Medical nutrition therapy is one of the recommended diabetes control measures. Lack of education, understanding of diet, and family support causes many DM patients to not comply with diet therapy recommendations. The purpose of this activity is to provide health education (health promotion) regarding medical nutrition therapy for DM treatment to type 2 DM patients in the agricultural community, conduct a meal planning simulation (DM diet) that is in accordance with the condition of type 2 DM patients, and increase the knowledge and skills of type 2 DM patients in medical nutrition therapy. The method that will be used is health education (promotion) on medical nutrition therapy for type 2 DM patients and a meal planning simulation regarding the DM diet. The results of the evaluation of the implementation of community service showed that there was an increase in the knowledge of participants by 90% to a good knowledge, 10% of participants had a moderate knowledge, and no participants had a poor knowledge of the definition of DM, symptoms and signs, risk factors, treatment/therapy, disease prevention, prevention of complications, medical nutrition therapy/DM diet, exchange foods, recommended and not recommended foods for DM patients and myths and facts about type 2 DM. The average pre-test result was 52.5 and increased in the post-test result of 82. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant difference in the pre-test and post-test values ​​of community service participants (p = 0.000). The activity of increasing knowledge and skills regarding medical nutrition therapy for type 2 diabetes mellitus patients in the agricultural community is a way to improve the ability of the community, especially type 2 DM patients, in managing medical nutrition therapy for type 2 DM, as an effort to prevent worsening and complications. The activity of increasing understanding and skills regarding medical nutrition therapy for type 2 diabetes mellitus patients in the agricultural community has proven effective.